Cambridge lower secondary English learner's book 8 - Elsdon, Graham (United kingdom : Cambridge university press, 2021)
The Cambridge Lower Secondary English Learner's Book 8 is designed for 8th-grade students and continues to build on the English language skills developed in earlier stages. This book focuses on improving students' proficiency in reading, writing, listening, and speaking, with a more advanced and varied selection of texts and activities. It emphasizes critical thinking, creativity, and language analysis, helping students express themselves clearly and confidently.
Keywords: English : Textbook